Effect of CSF biomarkers on cortical thickness in males and females. (31st December 2021) - Sangha, Oshin; Lee, Sieun; Ma, Da; Popuri, Karteek; Wang, Lei; Beg, Mirza Faisal
Abstract: Background: The level of elevated Tau, phosphorylated Tau, and aggregated Amyloid β in the cerebrospinal fluid (CSF) are markers of Alzheimer's pathology in the brain. In this study, we analyzed how these CSF biomarkers are related to the cortical thickness in males and females, for subjects who are cognitively normal (CN), with mild cognitive impairment (MCI), and diagnosed as Alzheimer's disease (AD). Method: We studied the CN (305), MCI (264) and AD (230) subjects from the ADNI dataset at baseline. We first studied the CSF biomarker level differences between males and females in all three groups. The effect of age was controlled using general linear models (GLM) We also looked at the effect of the CSF biomarkers on cortical thickness maps generated separately for males and females for all three groups, also with GLM‐based covariate regression to control the effect of age, ICV, and field strength of the scan. Result: For the CSF biomarker levels, we observed Tau to be significantly higher in females in the AD group. No other significant sex difference in the biomarker levels were observed. We found MCI males [Figure 1] and AD [Figure 2] females showing a negative relationship between Tau and thickness. When comparing CSF pTau levels to cortical thickness, a negative correlation was found only in males [Figure 3] for the AD group. When comparing Aβ and cortical thickness, negative correlations were found for males in the CN [Figure 4] and AD group [Figure 5], and for females [Figure 6] in the MCI group. Conclusion: The results suggest that the relationship between cortical thickness and CSF biomarkers is different in males and females in CN, MCI, and AD groups. We found that there is a negative relationship between CSF biomarkers and cortical thickness.